Occupational Therapy Practice with Adults with Intellectual Disability: What More Can We Do? - Khalilah R. Johnson; Meghan Blaskowitz; Wanda Mahoney (Scholarworks @ WMU, 2019)
In this Opinions in the Profession paper, we explore how occupational therapists can better address the occupational needs of adults with ID. We describe the facilitators and barriers to occupational therapists' work with this population, and we provide recommendations that align with broader efforts of national, state, and community-based organizations aimed at improving the lives of adults with ID.